2006
DOI: 10.1111/j.1464-410x.2006.06378.x
|View full text |Cite
|
Sign up to set email alerts
|

Injectable polydimethylsiloxane for treating incontinence in children with the exstrophy‐epispadias complex: long‐term results

Abstract: In this section authors from the UK describe their experience with plastic injections for treating incontinence in children with the exstrophy‐epispadias complex, finding that in the long term the success rate was reasonable, although the injections often needed to be repeated. Authors from Brazil present an analysis of anomalies of the epididymis and processus vaginalis in human fetuses, and in patients with cryptorchidism treated and untreated with hCG. OBJECTIVE To present our experience with the use of inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
3
20
2
1
Order By: Relevance
“…Table 4 summarizes the results of previous reports and our study regarding the success rates for IBA, and in particular the rates of achieving complete dryness after unsuccessful BNR for patients with N-ISD and A-ISD. [10][11][12][13][14][15][16][17] Although the success rates in previous reports averaged 31% (range: 7-70%), the rate in our study (100%) was substantially higher. To our best knowledge, there have been only 2 reports on IBA after the PSP, by Kitchens et al 16 and Misseri et al 17 (Table 4) Complete dryness was achieved in 2/11 (18%), including 1 patient who underwent the PSP.…”
Section: Discussioncontrasting
confidence: 75%
“…Table 4 summarizes the results of previous reports and our study regarding the success rates for IBA, and in particular the rates of achieving complete dryness after unsuccessful BNR for patients with N-ISD and A-ISD. [10][11][12][13][14][15][16][17] Although the success rates in previous reports averaged 31% (range: 7-70%), the rate in our study (100%) was substantially higher. To our best knowledge, there have been only 2 reports on IBA after the PSP, by Kitchens et al 16 and Misseri et al 17 (Table 4) Complete dryness was achieved in 2/11 (18%), including 1 patient who underwent the PSP.…”
Section: Discussioncontrasting
confidence: 75%
“…After a mean follow-up of 12.5 years, continence or partial continence was achieved in 98% of the patients (most of these patients had also undergone bladder augmentation); however, only seven patients (18%) achieved continence with bladder-neck reconstruction alone, only 10 patients (21%) overall were able to void volitionally without intermittent catheterization (CIC), and 33 patients (69%) underwent bladder augmentation. Similar to the experience by Burki et al [25,26], they found that redo bladder-neck reconstruction alone could not produce continence in their patients; however, with bladder augmentation most achieved continence (91%).…”
Section: Continencesupporting
confidence: 72%
“…Burki et al [25] reported results using polydimethylsiloxane injected at the bladder neck for treatment of incontinence in 52 patients. Continence was defined as complete dryness.…”
Section: Continencementioning
confidence: 97%
“…Several authors mention that surgery at the bladder neck after injection(s) of Deflux or Macroplastique was not considered more difficult than in non-injected patients [6,8,9]; however, there is usually no mention of the technique used or of the results achieved. We have addressed these two points in the current study.…”
Section: Discussionmentioning
confidence: 97%